Diagnosis and typing of influenza using fluorescent barcoded probes. Issue 1 (December 2017) - Huang, Bixing; West, Nicholas; Vider, Jelena; Cox, Amanda; Constantino, Tanya; Harrower, Bruce; Pyke, Alyssa; McMahon, Jamie; Northill, Judith; Riordan, Tim; Warrilow, David
Abstract In this work, we explore a new hybridization technology using barcoded probes which has large-scale multiplexing capability. We used influenza virus to test whether the technology has application in virus diagnostics. Typing of influenza virus strains is an important aspect of global health surveillance. Standard typing procedures use serological or amplification-based assays performed sequentially. By comparison, the hybridization technology was correctly able to detect, type and subtype influenza A and B virus strains directly from clinical samples in a single reaction without prior virus isolation or amplification. Whilst currently not as sensitive as amplification-based assays, these results are a first-step towards application of this technology to the detection and typing of influenza and other viruses.